THE IMPLICATURE OF PUBLIC ADVERTISEMENTS IN PALEMBANG - Hasri Juliani; Ferry Kurniawan (Jotika Journal in Education, 2022)
Public advertising is advertising that is used to convey information, persuade or educate the reader or audience of the advertisement. Public advertising is designed for the benefit and welfare of society. The purpose of this study was to analyze the implicature of public advertisements in Palembang which includes the types of implicatures contained in advertisements and to find out how many students understand the meaning of these advertisements. The research method used is a qualitative-descriptive approach with observation data collection techniques and questionnaires. The sampling technique used was purposive sampling technique, in order to obtain a sample of 20 respondents from the English Literature study program at Bina Darma University. The analytical tool used is qualitative analysis, the results of the study prove that "Implicature of Public Advertising in Palembang" can be interpreted that all dominant public advertisements use conventional types of implicatures, so that advertisements become more easily understood by the public. Overall, students are able to understand advertisements and give very precise and balanced implications for each other or have almost the same implications.